Characteristics and outcome of pediatric renal cell carcinoma patients registered in the International Society of Pediatric Oncology (SIOP) 93‐01, 2001 and UK‐IMPORT database: A report of the SIOP‐Renal Tumor Study Group. Issue 11 (3rd February 2021) - van der Beek, Justine N.; Hol, Janna A.; Coulomb‐l'Hermine, Aurore; Graf, Norbert; van Tinteren, Harm; Pritchard‐Jones, Kathy; Houwing, Maite E.; de Krijger, Ronald R.; Vujanic, Gordan M.; Dzhuma, Kristina; Schenk, Jens‐Peter; Littooij, Annemieke S.; et al.
Abstract: In children, renal cell carcinoma (RCC) is rare. This study is the first report of pediatric patients with RCC registered by the International Society of Pediatric Oncology‐Renal Tumor Study Group (SIOP‐RTSG). Pediatric patients with histologically confirmed RCC, registered in SIOP 93‐01, 2001 and UK‐IMPORT databases, were included. Event‐free survival (EFS) and overall survival (OS) were analyzed using the Kaplan‐Meier method. Between 1993 and 2019, 122 pediatric patients with RCC were registered. Available detailed data (n = 111) revealed 56 localized, 30 regionally advanced, 25 metastatic and no bilateral cases. Histological classification according to World Health Organization 2004, including immunohistochemical and molecular testing for transcription factor E3 (TFE3) and/or EB (TFEB) translocation, was available for 65/122 patients. In this group, the most common histological subtypes were translocation type RCC (MiT‐RCC) (36/64, 56.3%), papillary type (19/64, 29.7%) and clear cell type (4/64, 6.3%). One histological subtype was not reported. In the remaining 57 patients, translocation testing could not be performed, or TFE‐cytogenetics and/or immunohistochemistry results were missing. In this group, the most common RCC histological subtypes were papillary type (21/47, 44.7%) and clear cell type (11/47, 23.4%). Ten histological subtypes were not reported. Estimated 5‐year (5y) EFS and 5y OS of the total group was 70.5% (95% CI = 61.7%‐80.6%) and 84.5% (95% CI = 77.5%‐92.2%), respectively. Estimated 5y OS for localized, regionally advanced, and metastatic disease was 96.8%, 92.3%, and 45.6%, respectively. In conclusion, the registered pediatric patients with RCC showed a reasonable outcome. Survival was substantially lower for patients with metastatic disease. This descriptive study stresses the importance of full, prospective registration including TFE‐testing. Abstract : What's new? Pediatric renal cell carcinoma (RCC) is a rare malignancy, knowledge of which is based largely on adult RCC. Here, pediatric RCC was retrospectively studied using data from the International Society of Pediatric Oncology – Renal Tumor Study Group (SIOP‐RTSG). Pediatric RCC patients had a 5‐year overall survival rate of 84.5 percent, with notably lower survival for patients with metastatic disease. In pediatric RCC patients tested for transcription factor E3 and EB, 56.3 percent presented with translocation type. The findings highlight the importance of full registration of pediatric RCCs, with information on germline genetics and transcription factor testing.